Possibilities of surgical treatment for locally recurrent and complicated breast cancer - V. P. Letyagin; I. V. Kolyadina; I. V. Vysotskaya (ABV-press, 2015)
Tumor progression (distant metastases, local-regional recurrences, contralateral cancer) is a main cause of death in patients with breast cancer (BC). The occurrence of local recurrences is associated mainly with the nonradicality of surgery. Patient age, tumor subtype, and personalized systemic therapy have a statistically significant impact on the prediction of recurrence. It is most likely that the disease can come back as a local recurrence in the subgroups of nonluminal tumors with HER-2 overexpression and in those of triple negative cancer.The paper presents the data available in the literature and the authors' observations concerning the role and place of surgical treatment for locally recurrent BC. It gives major predictors of local and local-regional recurrences and defines main indications for different types of surgical interventions, including plastic surgery.